Gender Diversity on Commissioner Board and Decision Making: Evidence Using Capital Raised Through IPOs - Soesetio, Yuli; Rudiningtyas, Dyah Arini; Winarta, Winarta; Dhevi, Cattetiana (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This study aims to analyze the influence of the presence of women in the board of commissioners’ structure on the funds allocating decisions to finance various company investment opportunities sourced from corporate actions, such as an initial public offering (IPO). Service companies, especially the financial sector became a vast field for a woman, therefore, the financial sector that has conducted IPOs on the Indonesia Stock Exchange (IDX) for the past 21 years was selected as a research sample. The analytical tool used is multiple linear regression with OLS method which examines cross-sectionally the effect of the presence of women in 53 companies. This result shows that the presence of women on the board of commissioners affects the decision-making process on the amount of funding allocation for the company's investment opportunities. Their existence minimizes the allocation of IPO funds to finance various company investment opportunities in the future. Thus, gender studies in IPO corporate actions, especially in developing countries, are still very rarely studied. Women are known to have a short-term problem-solving perspective and are less confident than men, but they are more careful when making decisions. Despite the dominating nature of prudence, women can reduce the potential for financial distress due to risky investment decisions by choosing the decision to hoard funds in the form of cash to strengthen working capital.